The Evolution of Madness: A Characterization of Arthur Fleck in The Movie “Joker” (2019) by Todd Phillips - Dewi, Adelia Puspita; Wijaya, Mutiara Zaskia; Faisal, Faisal (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2025)
This study examines the evolution of Arthur Fleck into the Joker, exploring the psychological, social, and institutional factors contributing to his transformation. Utilizing a qualitative methodology, the research analyses Arthur Fleck's character through his experiences of trauma, societal rejection, and mental health struggles. Researchers watched the movie multiple times, analysed the script, and identified relevant dialogue or words for the character.  Key findings indicate that Arthur Fleck's descent into madness is shaped significantly by his childhood abuse, loneliness, and the systemic neglect he faces in Gotham City. The film serves as a critical commentary on contemporary issues surrounding mental health and societal responsibility, highlighting the urgent need for compassion towards marginalized individuals. This characterization not only reflects current societal anxieties but also emphasizes the impact of social dynamics on individual identity formation.